2020
DOI: 10.1017/s2045796020000657
|View full text |Cite
|
Sign up to set email alerts
|

Trends of the incidence of drug use disorders from 1990 to 2017: an analysis based on the Global Burden of Disease 2017 data

Abstract: Aim Drug use disorders are an important issue worldwide. Systematic attempts to estimate the global incidence of drug use disorders are rare. We aimed to determine the incidence of drug use disorders and their trends. Methods We obtained the annual incident cases and age-standardised incidence rate (ASR) of drug use disorders from 1990 to 2017 using the Global Health Data Exchange query tool. The estimated annual percentage changes of the ASR were used to quantify and evaluate the trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…That this population has grown is undisputed in the literature [8,23,30]. However, it is unclear to what extent evolving incidence rates of illicit drug use and overdose epidemics will impact upon mortality rates and the prevalence of drug use among older people in future [105][106][107]. There is a need to develop shared theories and frameworks and improve methodological rigour; clearly define and characterize the population of interest; shift from description to explanation; collect data on particularly marginalized older PWUD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…That this population has grown is undisputed in the literature [8,23,30]. However, it is unclear to what extent evolving incidence rates of illicit drug use and overdose epidemics will impact upon mortality rates and the prevalence of drug use among older people in future [105][106][107]. There is a need to develop shared theories and frameworks and improve methodological rigour; clearly define and characterize the population of interest; shift from description to explanation; collect data on particularly marginalized older PWUD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of DSM-V by the American Psychiatric Association included a shift from DSM-IV abuse and dependence to a category of use disorder, defined as mild, moderate, and severe in severity. Moderate to severe substance use disorders in DSM-V may be higher than DSM-IV and ICD-10 dependence, which means that if DSM-V prevalence estimates are used, the estimated burden of substance use disorders may be higher (Pan et al, 2020 ). Fourth, more and more evidence showed that there is a causal relationship between cannabis use and traffic accidents, and whether accidental injuries are included in the disease burden of CUD is still controversial.…”
Section: Limitationmentioning
confidence: 99%
“…From 1990 to 2019, the burden of substance use disorders has increased, including alcohol, amphetamines, cannabis, and cocaine as substance use disorders (Degenhardt et al, 2018 ; Pan et al, 2020 ; Whiteford et al, 2013 ). In this research, we analyzed data from the 2019 Global Burden of Disease Study (GBD) to estimate the incidence and prevalence of CUD and calculated the disease burden of CUD in 204 countries and territories and 21 regions over the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…This increase has occurred mostly in the regions with low, low-middle and middle socio-demographic index. Meanwhile, opioid use disorder (OUD) accounted for most of the cases with its proportion increasing from 47.18% in 1990 to 53.1% in 2017 ( 2 ), and continues to account for the largest burden of disease attributed to drug use ( 1 ).…”
Section: Introductionmentioning
confidence: 99%